Pengrajin Batik Besurek di Kota Bengkulu Tahun 1992-2020 - Fiana, Okta; Hardi, Etmi (Lembaga Yasin AlSys, 2024)
This research describes besurek batik craftsmen in Bengkulu City from 1992-2020. The emergence of many people in the city of Bengkulu who work as batik craftsmen in order to improve their welfare and fulfill their daily living needs. The aim of this research is to describe the development of besurek batik craftsmen in Bengkulu City and the influence of the emergence of besurek batik crafts on the socio-economic life of craftsmen in Bengkulu City. The method applied in this research is the historical method which consists of four stages, namely heuristics, criticism, interpretation and historiography. The first stage is heuristic which is the stage of collecting data. The author collects data related to research that adopts two types of sources, namely primary sources and secondary sources. Primary sources were obtained from the interview answer from besurek batik craftsmen, Bengkulu government employees and traditional leaders in Bengkulu City. Before the interview was conducted, the author had prepared an interview guide, namely main questions based on the problem. Meanwhile, secondary sources are obtained from books and articles related to the research problem. Second, source criticism of the data that has been obtained by re-testing the data obtained to verify the truth. Third, data interpretation. Fourth, historiography, namely the author rewrites the research results. Based on the results of the research, it can be seen that the Besurek batik craft business in Bengkulu City began to experience development in 1992 since the inauguration of the level I government regulation for the Bengkulu region to use Besurek Batik for students and civil servants. Besurek batik was originally introduced by Mrs. Aisiyah. The besurek batik craft industry business is a business that has been carried out for generations through non-official educational channels. The besurek batik craft business can be used as the main job for craftsmen in order to fulfill their living needs. The besurek batik craft industry business has a big influence on the socio-economic life of besurek batik craftsmen in Bengkulu City. The level of social welfare, health, education, and socio-economic life of craftsmen has increased significantly.